Body composition assessment and sarcopenia in patients with biliary tract cancer: A systematic review and meta-analysis. Issue 2 (February 2022) - Watanabe, Jun; Matsui, Ryota; Sasanuma, Hideki; Ishizaki, Yoichi; Fukunaga, Tetsu; Kotani, Kazuhiko; Sata, Naohiro
Summary: Background: Sarcopenia, as assessed by body composition, can affect morbidity and survival in several gastrointestinal cancer. However, the impact of sarcopenia, referring to both quantity and quality of skeletal muscle, in biliary tract cancer (BTC) is debatable. We aimed to investigate the impact of sarcopenia on morbidity and mortality in patients with BTC. Methods: Electronic databases and trial registries were searched through July 2021 to perform random-effects meta-analyses. Study selection, data abstraction and quality assessment were independently performed using the Grading of Recommendations, Assessment, Development, and Evaluation approach. Results: Twenty-nine studies (4443 patients) were included; 28 used computed tomography and one used dual-energy X-ray absorptiometry to assess body composition. Eighteen studies reported the impact of pre-operative sarcopenia on postoperative outcomes; namely, sarcopenia increased postoperative complications (risk ratio = 1.23, 95% confidence interval [CI] = 1.07 to 1.41; I 2  = 2%), and decreased recurrence-free survival (hazard ratio [HR] = 2.20, 95% CI = 1.75 to 2.75; I 2  = 0%) in multivariable analyses. Low muscle quantity (HR = 2.26, 95% CI = 1.75 to 2.92; I 2  = 66%) and quality (HR = 1.75, 95% CI = 1.33 to 2.29; I 2  = 50%) decreased overall survival in multivariable analyses. The certainty of the evidence was low because of heterogeneity and imprecision. Conclusions: In sarcopenia, low muscle quantity and quality by body composition conferred an independent risk of morbidity and mortality in patients with BTC. Further studies are needed to confirm these findings and mitigate risk.